Multiparticulate Systems of Meloxicam for Colonic Administration in Cancer or Autoimmune Diseases - Eva Navarro-Ruíz; Covadonga Álvarez-Álvarez; M Ángeles Peña; Carlos Torrado-Salmerón; Zaid Dahma; Paloma Marina de la Torre-Iglesias (MDPI AG, 2022)
The aim of this research is the development of new colonic release systems of meloxicam (MLX) a non-steroidal anti-inflammatory drug (NSAIDs) with pH and time-dependent vehicles for cancer or autoimmune diseases. The colon has a higher pH than the rest of the gastrointestinal tract (GIT) and this can be used as a modified release strategy. Eudragit® polymers are the most widely used synthetic products in the design of colonic release formulations because they might offer mucoadhesiveness and pH-dependent release. Colonic delivery systems produced with pH-dependent and permeable polymers (FS-30D) or with pH-independent and low permeability polymers (NM-30D), must dissolve at a pH range of 6.0-7.0 to delay the release of the drug and prevent degradation in the GIT, before reaching the colon. The conditions prepared to simulate a gastrointestinal transit showed the CNM multiparticulate system, composed of Eudragit® NM and cellulose, as the best release option for MLX with a more sustained release with respect to the other formulations. CNM formulation followed Higuchi and First-order release kinetics, thus MLX release was controlled by a combination of diffusion and polymers swelling/eroding processes.